PERANCANGAN SMART TRASH PENDETEKSI SAMPAH LOGAM DAN NON LOGAM BERBASIS ARDUINO UNO - Dedi Wahyudi (JURNAL PERANGKAT LUNAK, 2022)
Technological advances, especially in the field of microcontrollers and sensors, have had a major impact on human life. For example, in the field of cleanliness, automatic waste sorting must be done, because nowadays people do not have enough information about the environment, especially about waste disposal. Waste sorting aims to sort waste, in this case into metal and non-metal, so that the waste recycling process becomes more efficient. But in reality, types of waste are still mixed in landfills. Based on these problems, a garbage bin automation was created, a prototype of a microcontroller-based smart trash can whose main function is to sort waste, especially garbage that contains metal elements. Overall, the design of this tool was successful. This can be proven by the test results from a total of 36 (thirty six) respondents 28(78%) respondents answered the system is very interesting, 27(75%) respondents answered the system is very easy to use, 30(83%) respondents answered the system performance is very good, and 33 (92%) respondents answered the system was very useful.